Risk taking behaviour among early adolescents in Johor Bahru and its associated factors - M.A Rahmah; B Shahraniza (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : Social problems among adolescents are on the increasing trend. Their involvement in different kinds of high risk behaviours could lead them into juvenile delinquency. Early adolescence is the stage where they are easily influenced. However, this is the period where they should be captured for health prevention enhancement. Objectives : A cross-sectional study was carried out to identify factors associated with risk taking behaviours involving form one adolescents in selected secondary schools in Johor Bharu. Methods : Using self administered questionnaires, a total of 280 respondents were recruited via multi-stage sampling. Results : The prevalence of risk taking behaviour among respondents was 66.8%. Going to video games and karaoke centres was the most popular risk taking behaviour (46.8%) to be followed by truancy (30.7%). Among all the factors studied, being male (AOR=4.5, 95% CI 2.39-8.4), Malay (AOR=7.5, 95% CI 3.30-17.19), and having negative perception towards teachers (AOR 0.3, 95% CI 0.16-0.65) were risk factors for such behaviour among respondents. However, coming from an intact family (AOR=0.1), 95% CI 0.02-0.47) was found to be protective against risk taking behaviour. Conclusion : Intact family structure and having positive perception towards teachers were found to be protective against risk taking behaviours among adolescents.